Adiponectin Isoforms and Leptin Impact on Rheumatoid Adipose Mesenchymal Stem Cells Function - Urszula Skalska; Ewa Kontny (Stem Cells International)
Adiponectin and leptin have recently emerged as potential risk factors in rheumatoid arthritis (RA) pathogenesis. In this study we evaluated the effects of adiponectin and leptin on immunomodulatory function of adipose mesenchymal stem cells (ASCs) derived from infrapatellar fat pad of RA patients. ASCs were stimulated with leptin, low molecular weight (LMW) and high/middle molecular weight (HMW/MMW) adiponectin isoforms. The secretory activity of ASCs and their effect on rheumatoid synovial fibroblasts (RA-FLS) and peripheral blood mononuclear cells (PBMCs) from healthy donors have been analysed. RA-ASCs secreted spontaneously TGFβ, IL-6, IL-1Ra, PGE2, IL-8, and VEGF. Secretion of all these factors was considerably upregulated by HMW/MMW adiponectin, but not by LMW adiponectin and leptin. Stimulation with HMW/MMW adiponectin partially abolished proproliferative effect of ASC-derived soluble factors on RA-FLS but did not affect IL-6 secretion in FLS cultures. ASCs pretreated with HMW/MMW adiponectin maintained their anti-inflammatory function towards PBMCs, which was manifested by moderate PBMCs proliferation inhibition and IL-10 secretion induction. We have proved that HMW/MMW adiponectin stimulates secretory potential of rheumatoid ASCs but does not exert strong impact on ASCs function towards RA-FLS and PBMCs.